Bank service quality - Leong, Soo Hui (2008)
This Final Year Project (FYP) is based on a study of customer satisfaction about the level of service quality provided by banks in Singapore. The motivation of this study is triggered from the fact that the concept of providing superior service quality is receiving worldwide recognition across countries and industries.